Number 6
Answer:
y = (c - ax)/b
Step-by-step explanation:
ax + by = c
by = c - ax
y = (c - ax)/b
<em>I answered number 5 in your last question.</em>
Answer:
x-3y-z
Step-by-step explanation:
separate common terms and add them
1/2x+3/4x=1x
-2y-y=-3y
2z-3z=-1z
1x-3y-1z
7 - 9w = - 29
Subtract 7 from both sides
- 9w = - 36
Divide by - 9 on both sides
w = 4
Subtract 20n from both sides of the equation.
n^2+100-20n=0
factor using the perfect square rule.
(n-10)^2=0
set the n-10 equal to 0.
n-10=0
add 10 to both sides of the equation.
n=0
Answer:
Step-by-step explanation:
note : the area of a rectangle is : A = L ×W
L : lenght W : the width
A = (1/2)(3/8) = 3/16 m²